Optimizing the performance of MSMEs through financial reporting training - St Salmah Sharon; Muchtar Muchtar; Elia Ardyan; Adindah Novihartina Jafar; Yuyun Karystin Meilisa Suade; Novika Ayu Triany (University of Merdeka Malang, 2024)
The Moncongloe District is an environment that is rich in potential with many Micro, Small, and Medium Enterprises (MSMEs). Business owners in this sector face challenges in managing business finances effectively. Limited financial knowledge is due to the fact that MSMEs do not have a financial background or formal education in this field. This makes it difficult for MSMEs to understand the terms and concepts used in financial reports. This community empowerment program aims to make a positive contribution to business development in Moncongloe District, particularly in recording business finances. The implementation method is through workshops, discussions, questions and answers, and evaluations to provide an understanding of the importance of financial reports for MSMEs. The results of the community empowerment program show that workshop participants experienced an in-depth increase in knowledge about the importance of financial reports which can improve business performance for MSME entrepreneurs and Village-Owned Enterprises (BUMDES) in Moncongloe District, Maros Regency. In addition, participants succeeded in understanding the tools for starting a business, namely the Business Model Canvas, and making simple financial records that can help community empowerment partners in developing more structured and innovative MSME businesses.